Special high-flowability polyphenylene sulfide composition for nano injection molding and preparation method of special high-flowability polyphenylene sulfide composition
By using high-flow polyphenylene sulfide composition in nanoinjection molding technology, the problems of insufficient bonding strength, poor toughness and insufficient fluidity of modified polyphenylene sulfide materials in nanoinjection molding are solved, and higher adhesion, fluidity and multigravity properties are achieved, improving its application effect in nanoinjection molding process.
Patent Information
- Application Number
- CN202411949522.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-25
AI Technical Summary
The existing modified polyphenylene sulfide materials have defects such as insufficient metal bonding strength, poor toughness, and insufficient fluidity in nanoinjection molding technology, which limits their application.
A high-flow polyphenylene sulfide composition for nano injection molding is adopted, including polyphenylene sulfide resin, epoxy-containing copolymer, toughening agent, flow accelerator, glass fiber, antioxidant, lubricant and other additives. Through the reasonable proportion and synergistic effect of these components, the adhesion and flowability of the polyphenylene sulfide composition to metal is improved.
The adhesive strength of the polyphenylene sulfide composition and metal is significantly improved, the fluidity is improved, and the excellent notch impact strength, tensile strength and bending strength are taken into account, so that it can be better applied in the nano injection molding process.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a high-flow polyphenylene sulfide composition dedicated to nano injection molding and a preparation method thereof. Background Art
[0002] Nano injection molding (NMT) is a plastic-metal integrated molding technology first introduced by Taisei Co., Ltd. of Japan. Its technical route includes: 1. Use special chemical reagents to treat the metal surface to be processed (T treatment) to form a large number of nano-scale pits on the metal surface; 2. The plastic material is molded on the metal surface by injection molding, and the plastic melt instantly enters the T-treated pits on the metal surface to form a tightly combined "mortise and tenon" structure. This technology not only retains the texture of the metal, but also gives full play to the advantages of plastic materials such as lightweight and easy processing. It is currently widely used in smart phones, new energy vehicles and other 3C products. Common plastic materials such as PPE have insufficient fluidity and cannot fill the metal pits smoothly during molding; and materials such as PP and PE have low bonding strength with the metal surface (<100Kgf / cm 2 ), but not in the NMT field. Therefore, the fluidity of plastic materials and the adhesion of metals are two key indicators for NMT molding. As a special engineering plastic, modified polyphenylene sulfide (PPS) material has the advantages of high temperature resistance, corrosion resistance, flame retardancy, high strength, etc. It has been widely used in the fields of automobiles, consumer electronics, construction, mechanical processing, etc., and is an ideal special material for NMT. However, unmodified PPS has defects such as insufficient metal bonding strength, poor toughness, and insufficient fluidity, which limit its application in NMT.
[0003] In the related art, the patent document with publication number CN108250751A discloses a polyphenylene sulfide composition for NMT with a low dielectric constant and a preparation method. The patent document uses glycidyl ester copolymer, hollow glass microspheres, glass fiber and other additives to prepare a PPS composite material. The adhesion of the PPS composite material to metal reaches 220Kgf / cm 3 At the same time, the dielectric constant is 3.10, but the hollow glass microspheres in this method are prone to cracking and failure, and the processing equipment and conditions are more stringent, and the adhesion with metals needs to be improved. In addition, the amount of inorganic filler added is high, which reduces the overall fluidity of the material, and the plastic melt may not be able to flow smoothly into the T-treated micropores. Summary of the invention
[0004] The invention provides a high-flow polyphenylene sulfide composition specially used for nano injection molding and a preparation method thereof, which are used to solve the problems of insufficient adhesion between existing modified polyphenylene sulfide materials and metals and poor fluidity.
[0005] According to a first aspect of the present invention, the present invention provides a high-flow polyphenylene sulfide composition dedicated to nano injection molding, which comprises the following components in parts by weight: 55.0-75.0 parts of polyphenylene sulfide resin, 2.0-6.0 parts of epoxy-containing copolymer, 1.0-6.0 parts of toughening agent, 2.0-10.0 parts of flow promoter, 15.0-25.0 parts of glass fiber, 0.05-0.50 parts of antioxidant, 0.1-5.0 parts of lubricant and 0.1-5.0 parts of other additives.
[0006] The polyphenylene sulfide composition of the present invention introduces an epoxy-containing copolymer, wherein the epoxy group can be ring-opened during extrusion processing to generate a grafting reaction with the functional group -SH at the end of the polyphenylene sulfide chain, and the epoxy polymer grafted at the end of the polyphenylene sulfide chain plays a role in connecting with the metal material, thereby enhancing the interface strength between the polyphenylene sulfide and the metal material, thereby improving the adhesion between the polyphenylene sulfide composition and the metal material. The main function of the flow promoter in the polyphenylene sulfide composition is to reduce the melt viscosity, improve the dispersibility, improve the compatibility, enhance the rheological properties and mechanical properties, and improve the processing fluidity, thereby improving the overall performance and processing efficiency of the PPS composite material. The polyphenylene sulfide composition of the present invention limits the amounts of polyphenylene sulfide resin, epoxy-containing copolymer, toughening agent, flow promoter, glass fiber, antioxidant, lubricant and other additives within a reasonable range, so that the components can play a better synergistic role, improve the adhesion between the polyphenylene sulfide composition and metal, improve the fluidity of the polyphenylene sulfide composition, and also take into account excellent notched impact strength, tensile strength and flexural strength, so that the composition can be better applied in the nano injection molding process.
[0007] In order to better improve the overall performance of the polyphenylene sulfide composition, the following components are further included, calculated by weight: 65-75 parts of polyphenylene sulfide resin, 4-5 parts of epoxy copolymer, 1-3 parts of toughening agent, 5-6 parts of flow promoter, 18-22 parts of glass fiber, 0.1-0.3 parts of antioxidant, 0.4-0.6 parts of lubricant and 0.4-0.6 parts of other additives.
[0008] Furthermore, the epoxy-containing copolymer is selected from one or more of methyl oxirane polymer, bisphenol A-epichlorohydrin copolymer, o-cresol novolac epoxy resin, and dicyclopentadiene (DCPD) phenol epoxy resin. The above-mentioned epoxy-containing copolymer can improve the adhesion between the polyphenylene sulfide composition and the metal, while having excellent flow properties.
[0009] Furthermore, the epoxy equivalent of the epoxy-containing copolymer is 1000-6000 g / eq. The present invention has found through experiments that the epoxy equivalent of the epoxy-containing copolymer has a great influence on the adhesion between the polyphenylene sulfide composition and the metal. The epoxy-containing copolymer in a reasonable epoxy equivalent range can improve the adhesion between the polyphenylene sulfide composition and the metal, while having excellent flow properties. When using an epoxy copolymer with a lower epoxy equivalent (epoxy equivalent less than 1000), the polyphenylene sulfide composition maintains good fluidity, but has low adhesion to metal materials; when using an epoxy copolymer with a higher epoxy equivalent (epoxy equivalent greater than 6000), the fluidity of the polyphenylene sulfide composition is greatly reduced, and the adhesion to the metal material is not significantly improved.
[0010] Furthermore, the epoxy equivalent of the epoxy-containing copolymer is preferably 2000-4000 g / eq.
[0011] The weight average molecular weight of the epoxy-containing copolymer has a significant effect on the mechanical properties, processing properties, heat resistance, compatibility, molecular weight distribution and softening point of the polyphenylene sulfide composition. In order to improve the overall properties of the polyphenylene sulfide composition such as mechanical properties and processing properties, the weight average molecular weight of the epoxy-containing copolymer is 1000-10000, preferably 3000-8000, and more preferably 5000-6000.
[0012] Furthermore, the flow modifier is a liquid crystal polymer. The present invention introduces a liquid crystal polymer (LCP) as a flow promoter, which can improve the fluidity of the polyphenylene sulfide composition, weaken the disentanglement between molecular chains during molding, reduce flow resistance, improve fluidity, and enable the plastic melt to smoothly fill the micropores on the surface of the metal material.
[0013] Furthermore, the flow modifier is preferably a thermotropic liquid crystal polymer. By utilizing the property of thermotropic LCP that it changes from a crystalline state to a liquid crystal state during the heating process, the disentanglement between molecular chains can be more effectively weakened during molding, the flow resistance can be more effectively reduced, the fluidity can be improved, and the plastic melt can more smoothly fill the micropores on the surface of the metal material. The flow modifier is more preferably a thermotropic liquid crystal polymer with a melting point of 220-280°C.
[0014] Furthermore, the weight average molecular weight of the liquid crystal polymer is 1000-8000, preferably 3000-6000. The weight average molecular weight of the liquid crystal polymer has a significant effect on the mechanical properties, processing properties, heat resistance, compatibility, molecular weight distribution and softening point of the polyphenylene sulfide composition. The liquid crystal polymer with a weight average molecular weight in the above range can improve the overall properties of the polyphenylene sulfide composition, such as mechanical properties and processing properties.
[0015] Furthermore, the toughening agent is selected from one or more of maleic anhydride grafted ethylene-alpha olefin copolymer, ethylene-glycidyl methacrylate copolymer and ethylene-methyl acetic acid-glycidyl methacrylate copolymer. The present invention can improve the dispersion performance of LCP in polyphenylene sulfide resin and enhance the interface effect between polyphenylene sulfide resin and LCP by adding an elastomer with a polar group as a toughening agent, thereby improving the strength and toughness of the polyphenylene sulfide composition.
[0016] The melt index of polyphenylene sulfide resin has an important influence on the processing fluidity, crystallization performance, thermal stability, molding shrinkage and mechanical properties of the polyphenylene sulfide resin composition. In order to improve the processing fluidity, thermal stability and other properties of the polyphenylene sulfide resin composition, further, the melt index of the polyphenylene sulfide resin is 500-1200g / 10min, preferably 800-1000g / 10min. The inventors also found that a certain amount of chlorine in the polyphenylene sulfide resin will affect the interfacial adhesion between the resin and the metal particle filler, and then affect the adhesion between the polyphenylene sulfide resin composition and the metal material. In order to avoid the influence of the chlorine content on the adhesion between the polyphenylene sulfide resin composition and the metal material, the present invention limits the chlorine content of the polyphenylene sulfide resin to ≤600ppm.
[0017] Furthermore, in the polyphenylene sulfide composition, the weight percentage of the polyphenylene sulfide resin is 45-80%, preferably 50-70%.
[0018] Glass fiber plays multiple roles in the polyphenylene sulfide composition, such as enhancing mechanical properties, improving toughness and increasing heat resistance. In order to better improve the overall performance of the polyphenylene sulfide composition, the glass fiber is further alkali-free glass fiber; the glass fiber can be alkali-free chopped glass fiber or continuous alkali-free glass fiber.
[0019] In order to better improve the overall performance of the polyphenylene sulfide composition, further, the diameter of the glass fiber is 9-25 μm.
[0020] Furthermore, the antioxidant is one or more of a hindered phenol antioxidant or a phosphite antioxidant; by selecting a suitable type of antioxidant, it is more conducive to improving the antioxidant and thermal stability properties of the polyphenylene sulfide composition.
[0021] Furthermore, the lubricant is selected from one or more of ethylene wax, pentaerythritol stearate or ethylene bisstearamide; by selecting a suitable type of lubricant, it is more conducive to improving the injection molding performance of the polyphenylene sulfide composition.
[0022] Furthermore, the other auxiliary agents include one or more of a heat stabilizer, a light stabilizer and a nucleating agent.
[0023] According to a second aspect of the present invention, the present invention also provides a method for preparing the above-mentioned polyphenylene sulfide composition, comprising the following steps: The polyphenylene sulfide resin, the epoxy-containing copolymer, the toughening agent, the flow promoter, the antioxidant, the lubricant and other additives are mixed to obtain a premix; The premix and glass fiber are mixed and extruded, drawn into strips, cooled, dried and granulated to obtain a polyphenylene sulfide composition.
[0024] Furthermore, the mixing time of the premix is 10-15 min.
[0025] Furthermore, during the mixing and extrusion process, the extruder temperature is set to 290-340° C., and the main engine speed is 300-550 rpm.
[0026] The polyphenylene sulfide composition of the present invention limits the dosage of polyphenylene sulfide resin, epoxy-containing copolymer, toughening agent, flow promoter, glass fiber, antioxidant, lubricant and other additives within a reasonable range, so that the components can play a better synergistic role, improve the adhesion between the polyphenylene sulfide composition and metal, improve the fluidity of the polyphenylene sulfide composition, and also take into account excellent notched impact strength, tensile strength and flexural strength, so that the composition can be better applied in the nano injection molding process. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in the field or the product instructions are used. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased through regular channels.
[0029] The raw materials used in the following examples and comparative examples are as follows: Polyphenylene sulfide resin: Zhejiang Xinhecheng Co., Ltd., polyphenylene sulfide resin 3450; Epoxy-containing copolymer: Nantong Xingchen Synthetic Materials Co., Ltd., Phoenix Epoxy Resin 0199; Flow promoter: Shenzhen Water New Materials Co., Ltd., LCP resin KD2.0; Toughener: Arkema Group, AX8900; Antioxidant: Aidico Corporation, AO-80; Lubricant: Emuri Group, Germany, VPG-861; Fiberglass: Jushi Group, ECS10-3-584; Other additives: Heat stabilizer: Qitai Technology Co., Ltd., S80; Light stabilizer: CYTEC Industrial, UV-5411; Nucleating agent: Xufeng Industry, talc powder 8000 mesh.
[0030] Examples 1-10 This embodiment provides a high-flow polyphenylene sulfide composition dedicated to nano injection molding, and its raw material composition is shown in Table 1 below in parts by weight.
[0031] The preparation method of the polyphenylene sulfide composition of this embodiment comprises the following steps: a. According to the proportion, add polyphenylene sulfide resin, epoxy-containing copolymer, flow promoter, toughening agent, antioxidant, lubricant and other additives into a premixer and mix for 10-15 minutes to obtain a premix.
[0032] b. Add the premix at the main feed port and the glass fiber at the side feed port.
[0033] c. Mix and extrude the materials from a twin-screw extruder, draw strips, cool, dry and granulate to obtain a modified composite material. The extruder temperature is set at 290-340°C and the main engine speed is 300-550 rpm.
[0034] Comparative Example 1 This comparative example provides a polyphenylene sulfide composition, and its raw material composition is shown in Table 1 below in terms of weight percentage, which is different from Example 6 in that no epoxy-containing copolymer is added. The preparation method of the polyphenylene sulfide composition of this comparative example does not add an epoxy-containing copolymer in step a, and the rest is the same as Example 6.
[0035] Comparative Example 2 This comparative example provides a polyphenylene sulfide composition, and its raw material composition is shown in Table 1 below in terms of weight percentage, which is different from Example 6 in that no flow promoter is added. The preparation method of the polyphenylene sulfide composition of this comparative example does not add a flow promoter in step a, and the rest is the same as Example 6.
[0036] Comparative Example 3 This comparative example provides a polyphenylene sulfide composition, and its raw material composition is shown in Table 1 below in terms of weight percentage, which is different from Example 6 in that no toughening agent is added. The preparation method of the polyphenylene sulfide composition of this comparative example does not add a toughening agent in step a, and the rest is the same as Example 6.
[0037] Comparative Example 4 This comparative example provides a polyphenylene sulfide composition, and its raw material composition is shown in Table 1 below in parts by weight, which is different from Example 6 in that the epoxy equivalent of the epoxy-containing copolymer is 400-800. The preparation method of the polyphenylene sulfide composition of this comparative example is the same as that of Example 6.
[0038] Comparative Example 5 This comparative example provides a polyphenylene sulfide composition, and its raw material composition is shown in Table 1 below in terms of weight parts, which is different from Example 6 in that the epoxy equivalent of the epoxy-containing copolymer is 8000-10000. The preparation method of the polyphenylene sulfide composition of this comparative example is the same as that of Example 6.
[0039] Comparative Example 6 This comparative example provides a polyphenylene sulfide composition, and its raw material composition is shown in Table 1 below in terms of weight percentage. The difference from Example 6 is that an equal amount of polyurethane polymer is used to replace the epoxy-containing copolymer. The preparation method of the polyphenylene sulfide composition of this comparative example does not add the epoxy-containing copolymer in step a, but adds the polyurethane polymer, and the rest is the same as Example 6.
[0040] Comparative Example 7 This comparative example provides a polyphenylene sulfide composition, and its raw material composition is shown in Table 1 below, in terms of weight percentage. The difference from Example 6 is that an equal amount of PEI is used to replace the thermotropic LCP. Wherein, PEI is from: SABIC, polyetherimide resin PEI, 1000EF. The preparation method of the polyphenylene sulfide composition of this comparative example is the same as that of Example 6.
[0041] The polyphenylene sulfide compositions obtained in the examples and comparative examples were subjected to performance tests according to the following test methods: Tensile strength: measured according to ISO527 standard.
[0042] Flexural strength: measured according to ISO 178 standard.
[0043] Impact strength: measured according to ISO179 standard.
[0044] Metal material pull-out test: The polyphenylene sulfide composition is injection molded on the surface of the magnesium alloy. The size of the magnesium alloy part is 44mm×18mm×1.5mm, the size of the polyphenylene sulfide part is 40mm×10.2mm×3mm, and the bonding area is 0.5cm 2 , and then conduct a tensile test at a speed of 10.0mm / min and take the maximum tensile value.
[0045] Material fluidity test: The polyphenylene sulfide composition melt is injected into the spiral flow mold cavity under fixed temperature and pressure, and the flow length is recorded. The injection molding machine model is Haitian injection molding machine KEBA-1075.
[0046] The performance test results of the polyphenylene sulfide compositions obtained in the examples and comparative examples are shown in Table 2 below.
[0047] Table 1 Table 2
[0048] It can be seen from the experimental data in Table 2 that the polyphenylene sulfide composition of the present invention can improve the adhesion between the polyphenylene sulfide composition and the metal by adding an appropriate proportion of the epoxy-containing copolymer and limiting the amount of the polyphenylene sulfide resin, the epoxy-containing copolymer, the toughening agent, the flow promoter, the glass fiber, the antioxidant, the lubricant and other additives within a reasonable range, so that the components can play a better synergistic role (metal pull-out force ≥ 226Kgf / cm 2 ), and also solved the defect that the fluidity of the polyphenylene sulfide composition decreased significantly due to the thermal oxidative crosslinking after adding the epoxy-containing copolymer, so that the polyphenylene sulfide composition has good fluidity (flow length ≥305) and excellent notched impact strength (≥5.4KJ / m 2 ), tensile strength (≥144MPa) and flexural strength (≥103MPa), making it better used in nano injection molding process. Among them, the polyphenylene sulfide compositions of Examples 6 and 10 have better bonding performance and fluidity, and the metal pull-out force is greater than 250Kgf / cm 2 , flow length>400. The polyphenylene sulfide composition of Example 6 has the best metal adhesion and flow length, and also has good notched impact strength, tensile strength and flexural strength.
[0049] It can be seen from the results of Example 6 and Comparative Example 1 that adding a proper amount of the epoxy-containing copolymer to the polyphenylene sulfide composition can significantly improve the adhesion between the polyphenylene sulfide composition and the metal material, and can also enable the polyphenylene sulfide composition to maintain good fluidity.
[0050] It can be seen from the results of Example 6 and Comparative Example 2 that after the flow promoter LCP is added to the polyphenylene sulfide composition, the flow length of the polyphenylene sulfide composition is significantly improved; in addition, due to the addition of LCP, the notched impact strength of the polyphenylene sulfide composition tends to decrease. This is because LCP itself has poor toughness and is not impact-resistant, and the compatibility of the two polymers of polyphenylene sulfide resin and LCP is poor, resulting in a loss in performance of the polyphenylene sulfide composition.
[0051] It can be seen from the results of Example 6 and Comparative Example 3 that after the toughening agent is added to the polyphenylene sulfide composition, the notched impact strength is significantly improved. This is because the polar groups (maleic anhydride / glycidyl methacrylate) in the toughening agent improve the compatibility of the polyphenylene sulfide resin and the LCP phase, thereby improving the toughness. It can be further seen from the results of Examples 6, 7 and 10 that when the amount of the toughening agent is increased, the strength of the polyphenylene sulfide composition decreases due to the low strength and low modulus of the toughening agent itself. Therefore, the best effect is achieved when the mass ratio of the toughening agent is 3.0%.
[0052] It can be seen from the results of Example 6 and Comparative Examples 4 and 5 that after using an epoxy-containing copolymer with a lower epoxy equivalent (epoxy equivalent of 400-800), the polyphenylene sulfide composition maintains good fluidity, but has low adhesion to metal materials; after using an epoxy-containing copolymer with a higher epoxy equivalent (epoxy equivalent of 8000-10000), the fluidity of the polyphenylene sulfide composition is greatly reduced, and the adhesion to metal materials is not significantly improved; therefore, the epoxy-containing copolymer with an epoxy equivalent in the range of 2000-4000 is the best for the polyphenylene sulfide composition.
[0053] It can be seen from the results of Example 6 and Comparative Example 6 that, under the same dosage, the metal adhesion of the polyphenylene sulfide composition using the epoxy-containing copolymer is higher than that of the polyphenylene sulfide composition using the polyurethane polymer. Therefore, in this system, the epoxy-containing copolymer is more suitable than the polyurethane polymer.
[0054] It can be seen from the results of Example 6 and Comparative Example 7 that the selection of the type of flow promoter is also very important. Compared with the flow promoter PEI, the polyphenylene sulfide composition of the present invention uses the flow promoter LCP to form a better synergistic effect with the specific type of polyphenylene sulfide resin, epoxy-containing copolymer, toughening agent, glass fiber, antioxidant, lubricant and other additives of the present invention, thereby improving the metal adhesion and flow length of the polyphenylene sulfide composition.
[0055] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A high-flow polyphenylene sulfide composition for nano injection molding, characterized in that: The composition comprises the following components in parts by weight: 55.0-75.0 parts of polyphenylene sulfide resin, 2.0-6.0 parts of epoxy-containing copolymer, 1.0-6.0 parts of toughening agent, 2.0-10.0 parts of flow promoter, 15.0-25.0 parts of glass fiber, 0.05-0.50 parts of antioxidant, 0.1-5.0 parts of lubricant and 0.1-5.0 parts of other auxiliary agents.
2. The polyphenylene sulfide composition according to claim 1, characterized in that The epoxy-containing copolymer is selected from one or more of methyl oxirane polymer, bisphenol A-epichlorohydrin copolymer, o-cresol novolac epoxy resin, and dicyclopentadiene phenol epoxy resin.
3. The polyphenylene sulfide composition according to claim 1 or 2, characterized in that: The epoxy equivalent of the epoxy group-containing copolymer is 1000-6000 g / eq, preferably 2000-4000 g / eq; And / or, the weight average molecular weight of the epoxy-containing copolymer is 1000-10000, preferably 3000-8000, more preferably 5000-6000.
4. The polyphenylene sulfide composition according to any one of claims 1 to 3, characterized in that The flow modifier is a liquid crystal polymer, preferably a thermotropic liquid crystal polymer, more preferably a thermotropic liquid crystal polymer having a melting point of 220-280°C; Preferably, the weight average molecular weight of the liquid crystal polymer is 1000-8000, preferably 3000-6000.
5. The polyphenylene sulfide composition according to any one of claims 1 to 4, characterized in that: The toughening agent is selected from one or more of maleic anhydride grafted ethylene-α-olefin copolymer, ethylene-glycidyl methacrylate copolymer and ethylene-methyl propyl acetate-glycidyl methacrylate copolymer.
6. The polyphenylene sulfide composition according to any one of claims 1 to 5, characterized in that: The composition includes the following components in parts by weight: 65-75 parts of polyphenylene sulfide resin, 4-5 parts of epoxy-containing copolymer, 1-3 parts of toughening agent, 5-6 parts of flow promoter, 18-22 parts of glass fiber, 0.1-0.3 parts of antioxidant, 0.4-0.6 parts of lubricant and 0.4-0.6 parts of other auxiliary agents.
7. The polyphenylene sulfide composition according to claim 1, characterized in that: The melt index of the polyphenylene sulfide resin is 500-1200 g / 10 min, preferably 800-1000 g / 10 min; the chlorine content of the polyphenylene sulfide resin is ≤600 ppm; And / or, in the polyphenylene sulfide composition, the weight percentage of the polyphenylene sulfide resin is 45-80%, preferably 50-70%.
8. The polyphenylene sulfide composition according to claim 1, characterized in that: The glass fiber is an alkali-free glass fiber; and / or the glass fiber has a diameter of 9-25 μm.
9. The polyphenylene sulfide composition according to claim 1, characterized in that: The antioxidant is one or more of a hindered phenol antioxidant or a phosphite antioxidant; And / or, the lubricant is selected from one or more of ethylene wax, pentaerythritol stearate or ethylene bisstearamide; And / or, the other auxiliary agents include one or more of a heat stabilizer, a light stabilizer and a nucleating agent.
10. The method for preparing the polyphenylene sulfide composition according to any one of claims 1 to 9, characterized in that: The steps include: The polyphenylene sulfide resin, the epoxy-containing copolymer, the toughening agent, the flow promoter, the antioxidant, the lubricant and other additives are mixed to obtain a premix; The premix and glass fiber are mixed and extruded, drawn into strips, cooled, dried and granulated to obtain a polyphenylene sulfide composition.
Citation Information
Patent Citations
Polyphenylene sulfide resin composition with low dielectric constant and used for NMT (Nano Molding Technology) and preparation method
CN108250751A
Polyphenylene sulfide / carbon fiber composite material with good adhesion to metals
CN109535716A
Antenna cover comprising polymer composition having low dielectric constant and dissipation factor
CN114930638A
Polyarylene sulfide composition with improved adhesion to metal components
CN118109049A